Gendered domestic violence and abuse in popular culture - Ramon, Shulamit; Lloyd, Michele; Penhale, Bridget (Bingley, U.K. : Emerald Publishing Limited, 2020)
As binge-watching and streaming lead to increasing amounts of content and screen time, understanding how domestic violence and abuse is portrayed in popular culture and its impact on DVA in our society is more important than ever. This collection demonstrates how networked communication is influencing activism, both online and in the real-world.
Prelims -- Prologue Gendered domestic violence and abuse, popular culture and the digital revolution -- Chapter 1 Death foretold: a multiperspective study of domestic violence in an Italian town -- Chapter 2 Examining domestic violence and abuse in mainstream and social media: representations and responses -- Chapter 3 Hollywood and beyond: rescreening domestic violence -- Chapter 4 Leslie Morgan Steiner: an analysis of TED lectures on domestic violence by men towards women -- Chapter 5 The Australian media and child abuse -- Chapter 6 Elder abuse and media representation of abuse in family settings -- Chapter 7 News media representation of domestic violence victims and perpetrators: focus on gender and sexual orientation in international literature -- Chapter 8 Moral panic in the media: scapegoating South Asian men in cases of sexual exploitation and grooming -- Chapter 9 'stories not bouquets!': the #Metoo campaign in Slovenia and its social consequences -- Epilogue Gendered domestic violence and abuse in popular culture: where we are and where we would like to be -- Index.
Includes index.
Print version record.
Keywords: Family violence in popular culture; Family & Relationships, Abuse -- General; Domestic violence